Resolution of Case Of Abuse Against Child Offenders (Comparatory Study Between Bali Customary Law And National Law) - Lumira, Holys Abdiel (Westscience Press, 2024)
In Indonesia, there is one crime that occurs in the environment of children, known as the crime of abuse or often known as bullying. Bullying cases not only require national law but also customary law. In principle, the settlement of cases in customary criminal law with national law, especially in the handling of crimes committed by children, is the same as in national law in resolving cases using restorative justice whose resolution involves the perpetrator, victim, family of the perpetrator/victim and other parties. Related parties to jointly seek a just solution. In customary criminal law, a similar approach is taken by Adat leaders involving perpetrators, victims, families of perpetrators/victims and other related parties to seek Settlement based on Awig-awig, agreed upon and also using the norms prevailing in Adat people. In the process, it is carried out before the case in question is brought to court, while the settlement through restorative justice is carried out with trial proceedings. The sanction in customary crimes will be imposed if the person concerned repeats the same mistake. In this study, the autors uses normative legal research, which focuses on positive legal norms, the Child Criminal Justice System and Costumary law in Bali, especially Klungkung and Tabanan areas.